Design of An Agricultural Extension Schedule Management System - Soedarto, Teguh; Aditiawan, Firza Prima; Putra, Adzanil Rachmadhi (Inspiration: Jurnal Teknologi Informasi dan Komunikasi, 2023)
Based on the strategic plan of the Ministry of Agriculture for 2015-2019, development in the agricultural sector will refer to the Agriculture for Development Paradigm which positions the agricultural sector as a driver of balanced and comprehensive development transformation including demographic, economic, intersectoral, spatial, institutional and development governance. With such great potential, the Pasuruan Regency Food and Agriculture Security Service has problems in the availability of human resources in quantity, especially agricultural instructors. For this reason, there is a need for a system that can optimize existing human resources. The system development method used is the waterfall method, the waterfall method is a method that works sequentially, the development of the agricultural extension schedule management system has been going well. So that it can help the work management process of agricultural instructors in distributing agricultural extension at the village level. This agricultural extension schedule management system is implemented using a MySQL database and the PHP programming language. This system is easy to use so it helps related parties in schedule management and recording extension activities.